The Stock Market Premium, Production, and Relative Risk Aversion - Benninga, Simon; Protopapadakis, Aris (American Economic Review, 1991)
Higher relative risk aversion is associated with higher risk premiums only if the riskiness of output is exogenous. When consumers can affect the variability of output, the market risk premium may well decrease as the relative risk aversion increases. With constant relative risk aversion and linear production functions, the ratio of the market risk premium to the standard deviation of the market is constant and independent of the relative risk aversion. Copyright 1991 by American Economic Association.